Seasonal study of pollution and water degradation in the Sebou River basin Gharb region – Morocco - Slimane, Hamid; Belghiti, Driss; Ibrahimi, El mehdi Al; Azzouz, Essamri; Touhami, Ebn (Edelweiss Applied Science and Technology, 2025)
This study investigates the physicochemical characteristics of raw surface and groundwater in the Upper Sebou region to evaluate their suitability for irrigation and identify pollution sources. Seasonal field measurements were conducted in summer and winter, analyzing parameters such as pH, electrical conductivity, and major ion concentrations, including nitrates, chlorides, sulfates, sodium, calcium, magnesium, potassium, bicarbonates, and ammonium. Surface waters exhibit high mineral content year-round. The pH ranges from 8.06 to 8.65, indicating slightly basic conditions suitable for irrigation. Electrical conductivity varies between 520 and 16,320 µS/cm, with higher values in summer likely due to low river discharge and increased evaporation. Nitrate, chloride, and sulfate concentrations are generally elevated, reaching up to 830.88 mg/L, 868 mg/L, and 312.65 mg/L, respectively. Sodium levels reach 1,870 mg/L, reflecting contributions from both natural rock dissolution and anthropogenic activities. Groundwater shows seasonal pH variation, with slightly more acidic values in summer. Electrical conductivity ranges from 202 to 22,210 µS/cm, increasing during dry seasons due to ion concentration. Nitrate levels in wells exceed recommended thresholds in all samples, with maximum values of 884.10 mg/L in summer, suggesting contamination from fertilizers, organic waste, and domestic discharge. Ammonium exceeds WHO guidelines in 40% of wells; chloride and sodium surpass limits in 41% of samples. The findings confirm that both geochemical processes and human activities contribute to persistent nitrogen and salt pollution. Although some irrigation standards are met, elevated ion concentrations highlight the need for improved groundwater protection and wastewater management in the region.